Anti-Mullerian Hormone and Its Association with Polycystic Ovarian Syndrome: An Analytic Study - Oola Qzwini (Journal of Primary Care Specialties)
Objective: The aim of the study is to determine the association of anti-Mullerian hormone (AMH) with polycystic ovarian syndrome (PCOS). Background: Ovarian reserve refers to the fertility potential left within a woman’s two ovaries based on the number and quality of eggs. AMH is a clinical marker of female reproductive potential, and we aimed to determine whether it might be associated with PCOS. The criteria for diagnosis of PCOS are irregular ovulatory function (oligomenorrhea or amenorrhea), evidence of hyperandrogenism (biochemical or clinical), and the presence of a polycystic ovarian picture on sonography. Subjects and Methods: Two hundred couples were enrolled: 100 subfertile couples as a study group (n = 100) and 100 fertile couples as a control group (n = 100). Cycle day 2 (CD2) blood tests for AMH, follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone and clinical data such as height, weight, and waist and hip circumference measurements were performed for the females. Results: Thirty-seven percent of our study group have PCOS. The females with PCOS have a significant relationship with the age, AMH, and testosterone hormone. Subfertile women with PCOS have high level of AMH. Significant differences (P < 0.05) were identified in CD2 serum level of AMH and testosterone between the subfertile group and the fertile group. Both AMH and Testosterone were higher in the subfertile group than the control group, while FSH and LH demonstrates no significant difference. Conclusions: In comparison with healthy women, PCOS has a higher level of AMH; therefore, the management of PCOS has the potential of affecting ovarian functions and female fertility.